Pemanfaatan Teknologi Digital untuk Optimalisasi Pelayanan dan Dokumentasi Administratif melalui Web Desa Kentong, Lamongan - Eko Sutrisno; Lailatul Safitri; Lilla Puji Lestari; Ronny Makhfuddin Akbar; Yanuarini Nur Sukmaningtyas (Jurnal Ragam Pengabdian, 2025)
The development of digital technology has opened up opportunities for villages to improve the quality of public services and administrative documentation systems more efficiently and transparently. This service activity aims to improve the service and efficiency of village beautification, increase the capacity of village and kentong apparatus, Glagah District, Lamongan Regency in the use of information technology through training and socialization of village website management. The activity was carried out in the form of hands-on training for village officials and karangtaruna cadres regarding content management, information publication, and digital uploading of administrative documents from December 2024 to March 2025. The initial evaluation was conducted through questionnaires and brief interviews, which showed that most participants found the practical approach applied. However, it was found that there are still limitations in participants' confidence to manage websites independently, as well as the need for follow-up assistance, especially related to data security and digital document management. This activity is the first step in the digital transformation process at the village level. The limitation of this activity lies in the scope of implementation which is still limited to the initial socialization and training stage, without being followed by the full implementation stage and continuous monitoring. Follow-up in the form of technical assistance and advanced training is needed so that the use of the village web can run optimally and sustainably.